Digital Assistive Technology to Support Everyday Living in Community-Dwelling Older Adults with Mild Cognitive Impairment and Dementia - Holthe T (Clinical Interventions in Aging, 2022)
Torhild Holthe,1,2 Liv Halvorsrud,1,3 Anne Lund1 1Faculty of Health Sciences, Oslo Metropolitan University, Oslo, Norway; 2Norwegian National Centre for Ageing and Health, Vestfold Hospital Trust, Tønsberg, Norway; 3Faculty of Health and Welfare, Østfold University College, Halden, NorwayCorrespondence: Torhild Holthe, Faculty of Health Sciences, Oslo Metropolitan University, PO Box 4 St. Olavs plass, Oslo, 0130, Norway, Tel +47 911 34 088, Email torhol@oslomet.noObjective: The objective of this review was to explore whether knowledge about and practice of technology for older adults with mild cognitive impairment (MCI) and dementia (D) had developed since our 2017 review. Furthermore, we wanted to explore the usability and acceptability of technology in the newer trials, and how these may impact quality of life, occupational performance and human dignity.Materials and Methods: We searched for primary studies published between 2017 and 2020 reusing medical subject heading (MeSH) terms in five databases – Medline, PsycINFO, Embase, Amed and Cinahl – and obtained 1452 titles. The titles were divided in six piles, two for each of the three authors. The titles were sorted utilizing the Rayyan web tool. Fourteen studies were included in this review. The Mixed Method Appraisal Tool (MMAT) was used to assess the quality of the studies examined.Results: This review included almost twice as many participants as in the 2007– 2017 review. Since 2017, a shift seems to have occurred toward technologies that can be worn on the body to monitor body functions and report states, or imbalances. Moreover, research interest is now focused on mobile phone apps and wearables providing reminders and timely support, rather than on separate devices at home.Conclusion: The studies conducted since 2017 report on wearable and environmental digital assistive technologies and often with multiple purposes. Three strategies for support seem evident: prompting and reminding people with dementia, monitoring people with dementia at home using environmental sensors and biosensors and providing safety outdoors. Thus, there is still a need for further research on the impact of technologies promoting occupational performance, quality of life, and human dignity for independent living.Keywords: technology, Alzheimer’s disease, coping, ageing in place, quality of life, human dignity